PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN METODE EKSPERIMEN DI KELAS IV SD - HARTONO, RUDI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the reality on the SDN 19 Sungai Aur that learning is dominated by the teacher as a source of information. Teachers using the conventional method of teaching that resulted in a student science learning outcomes are low, for that researchers aim to discuss the increased yield learning science through experimental method in SDN 19 Class IV Sungai Aur West Pasaman. The approach used is a qualitative and quantitative approach consisting of two cycles includes four phases: planning, implementation, observation and reflection. The data of this study in the form of information about the process and outcome measures of data obtained from the observation and tests. Subjects were teachers, researchers (practitioners) and fourth grade students of SDN 19 classes totaling 20 people. Data analysis was performed using qualitative analysis and quantitative models. The results showed an increase. The increase can be seen from: a) the lesson plan (RPP) cycle I value the percentage is 74.5% (average) increased to 85.5% (good) in the second cycle. b) Implementation of experimental methods to study the aspects of teachers in the first cycle 78 (good) increased to 86% (very good) II.c cycle) implementation of learning with the experimental method in aspects of students' first cycle 72.5% (good) increased to 86% (very good) student learning outcomes in the first cycle value was 68.8 (moderately) increased to 78.8 (good) in the second cycle. So it can be concluded that the experimental method can improve student learning outcomes in learning science in the fourth grade at SDN 19 Sungai Aur.   Kata Kunci: hasil; belajar; IPA; metode; eksperimen